Vocational students and nicotine products: attitudes, beliefs and perspectives on health promotion - Vaihekoski, Anu (fi=Turun yliopisto|en=University of Turku|, 2026)
The use of nicotine products among young people is a global challenge. Alongside conventional tobacco, new nicotine products, such as e-cigarettes, have arrived. In Finland, young people in vocational education use tobacco, snus, and nicotine pouches, binge drink more often, and self-rate their health more poorly than other upper-secondary education students. They represent an important subgroup of young people and were chosen to be the target group of this PhD thesis. Young people’s health behaviours are strongly influenced by the health behaviours of their close circle. Peer influence remains a dominant factor. Individuals’ attitudes and perceptions toward nicotine products are connected to the initiation and continued use. Positive perceptions and social acceptance of nicotine use are associated with higher usage rates. The health behaviours established during adolescence have long-term implications for adult health. Schools can have an important role, and school-based substance use prevention programs are most effective with diverse, engaging activities, even though the evidence is limited. Young people’s health behaviour is a complex phenomenon. To understand their health behaviours and to promote health, it is essential to understand their attitudes, beliefs, and perceptions on health promotion. The PhD Thesis studied these factors among vocational students to support their substance-free living and health through a systematic review, quantitative, and qualitative data collection. The main findings were that vocational students' nicotine and other substance use decisions are shaped by personal values, confidence, and social influence, with peers and family playing a major role. Supportive relationships protect against use, whereas peer pressure and strict parental control can increase risk. Vocational students favour engaging, voluntary school-based programs, especially peer-led initiatives, and teachers as role models can affect their attitudes. At the societal level, students support stricter age-related controls, recognise social media’s impact, and value non-judgmental prevention approaches. The findings altogether describe the phenomenon of young people’s substance-free living and their perceptions of health promotion in the school environment.

Nuorten nikotiinituotteiden käyttö on maailmanlaajuinen haaste. Perinteisen tupakan rinnalle on tullut uusia nikotiinituotteita, kuten sähkösavukkeita. Suomessa ammatillisessa koulutuksessa opiskelevat nuoret käyttävät tupakkaa, nuuskaa, nikotiinipusseja, juovat humalahakuisesti useammin ja arvioivat terveytensä heikommaksi kuin muut toisen asteen opiskelijat. He muodostavat tärkeän nuorten alaryhmän ja valikoituivat siksi tämän väitöskirjan kohderyhmäksi. Nuorten terveyskäyttäytymiseen vaikuttavat vahvasti heidän lähipiirinsä terveyskäyttäytyminen, ja vertaisten vaikutus on edelleen merkittävä tekijä. Yksilön asenteet ja käsitykset nikotiinituotteista ovat yhteydessä käytön aloittamiseen ja jatkamiseen. Positiiviset käsitykset ja nikotiinin käytön sosiaalinen hyväksyntä liittyvät korkeampaan käyttöasteeseen. Nuoruudessa omaksutuilla terveyskäyttäytymisen tavoilla on pitkäaikaisia yhteyksiä aikuisuuden terveyteen. Kouluilla voi olla tärkeä rooli, ja koulupohjaiset ehkäisyohjelmat ovat tehokkaimpia, kun ne sisältävät monipuolisia ja osallistavia toimintoja, vaikka näyttö on vielä rajallista. Nuorten terveyskäyttäytyminen on monimutkainen ilmiö. Jotta heidän terveyskäyttäytymistään voidaan ymmärtää ja terveyttä edistää, on tärkeää tunnistaa heidän asenteensa, uskomuksensa ja käsityksensä terveyden edistämisestä. Väitöskirjassa tutkittiin näitä tekijöitä ammatillisissa oppilaitoksissa opiskelevien nuorten keskuudessa heidän päihteettömän elämänsä tukemiseksi systemaattisen kirjallisuus-katsauksen, määrällisen ja laadullisen aineiston kautta. Keskeiset tulokset osoittivat, että ammattiin opiskelevien nuorten päätöksiin nikotiinin ja muiden päihteiden käytöstä vaikuttavat henkilökohtaiset arvot, itsevarmuus ja sosiaalinen vaikutus, erityisesti vertaisten ja perheen rooli. Tukevat ihmissuhteet suojaavat käytöltä, kun taas vertaispaine ja tiukka vanhempien kontrolli voivat lisätä riskiä. Nuoret toivovat osallistavia ja vapaaehtoisia koulupohjaisia terveyden edistämisen toimia. Yhteiskunnallisella tasolla nuoret kannattivat tiukempia ikärajoihin liittyviä sääntelyjä, tunnistivat sosiaalisen median vaikutuksen ja arvostivat tuomitsemattomuutta. Tulokset kuvaavat nuorten päihteettömyyteen liittyviä tekijöitä ja heidän käsityksiään terveyden edistämisestä kouluympäristössä.